The Role of Andalusia as The Center of Islamic Civilization in The West - Inca Faizatun Nazwa; Ika Septiani; Aqil syaputra Syahputra; Wahyudin Wahyudin; Achmad Maftuh Sujana (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Andalusia is a region that has a strategic position in the history of the development of Islamic civilization in the Western world. During the period of Islamic rule, especially under the rule of the Umayyad Caliphate in Cordoba, the region developed into a highly developed center of science and culture. Andalusia became a symbol of the glory of Islam through progress in various fields such as education, philosophy, science, art, and architecture. Collaboration between Muslim, Jewish, and Christian scholars created a process of scientific and cultural exchange that gave birth to tremendous intellectual progress. This article aims to examine the role of Andalusia in the spread of Islamic civilization values to Europe and its influence on the development of science modern. This research uses a literature review method by tracing classical and contemporary historical sources related to Islamic civilization in Andalusia. The results of the study show that Andalusia was not only the center of government, but also an intellectual link between the Islamic world and the West, which made a great contribution to the emergence of the Renaissance era in Europe. Thus, Andalusia can be seen as one of the main foundations for the formation of world civilization based on Islamic values.